یوسف عزیز مگسیءِ راجی کرد: The role of Yousif Aziz Magsi in development of Baloch Nationalism - Dashti, Zahid; Durdana (Hanken, 2014)
Mir Yousuf Aziz Magasi was a young Baloch Political activist, Journalist and reformist who fought to the British Imperialist, despotic powers and tribal Sardars for the Baloch rights. In his age, Balochistan was enduring financially, educationally and socially, due to the English guideline and the brutalities of the tribal chiefs. He attempted to instruct the Baloch individuals, give them a feeling of patriotism, and flourish his people monetarily. His main goal was to fabricate educational institutions, and give the individuals a political sense. This paper centers the British imperialistic way to deal with the Baloch individuals, struggle of Mir Yousuf Aziz Magasi against the English Raj and giving a sense of identity to the people of Balochistan.